Procuring survival - Matilde Cappelletti; Leonardo M. Giuffrida (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
Public spending (i.e., 'G') enables governments to fulfill their fiscal policies. This paper takes a micro perspective and quantifies the impact of procurement spending - a specific component of G - on firm survival. We find that firms that receive public contracts survive longer, ceteris paribus, and that this effect accrues over time, reaching 20 percentage points after ten years. Our results are based on a novel dataset for Italy that combines balance sheet data on the universe of limited liability firms with administrative records on market entry and exit and quasi-universe of public contract data between 2008 and 2018. For construction auctions, we also rely on bid-level data to inform a regression discontinuity analysis. We find that the survival rate of winners relative to marginal losers is 70% higher after 36 months - or after two years and half of the median contract expiration. We explore several alternative channels that could rationalize our findings. We find that recipients do not become more productive, and their earnings become increasingly dependent on sales to public customers.
Keywords: D44; H32; H57; 330; firm survival; firm dynamics; government demand; public procurement; demandshocks; productivity; auctions; regression discontinuity design